Development of Basic Mechanical Tests for Malaysian Bamboos - Abang Ali, Abang Abdullah (1984)
Bamboo has found various applications, especially to the rural people but its potential as 1117· engineering material has not been fully realised because of a lack of knowledge of its strength properties. In the absence of 1% commonly accepted standard for the mechanical testing of bamboo, a procedure for basic strength tests was developed. Results for the strength properties of Bambusa vulgaris, locally known as Buluh Minyak, are presented.